2011
DOI: 10.1007/s11999-011-1934-7
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-stabilized Emulsion Increases Gentamicin Elution From Bone Cement

Abstract: Background Liquid antimicrobial use for antimicrobialloaded bone cement is limited because of decreased strength and small volume that can be loaded. Emulsifying the liquid antimicrobial into the monomer may address both issues. Questions/purposes We determined the effect of using a surfactant-stabilized emulsion on antimicrobial release, compressive strength, and porosity. Methods We made 144 standardized test cylinders from emulsified antimicrobial-loaded bone cement (three batches, 72 cylinders) and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The antimicrobial load must be low enough that the structural integrity of the cement fixation is not compromised [17,44]. Low-dose antimicrobial-loaded bone cement releases only a very small fraction of the drug load during the first week when it is needed [42,52,62]. Other investigational delivery vehicles, including calcium phosphate cements [30], hydroxyapatite composites [9,61], antibiotic implant coatings [2,3], and polymer beads/microparticles [4,46,47], also have drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial load must be low enough that the structural integrity of the cement fixation is not compromised [17,44]. Low-dose antimicrobial-loaded bone cement releases only a very small fraction of the drug load during the first week when it is needed [42,52,62]. Other investigational delivery vehicles, including calcium phosphate cements [30], hydroxyapatite composites [9,61], antibiotic implant coatings [2,3], and polymer beads/microparticles [4,46,47], also have drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the issue of phase separation, surfactants may be used. Miller et al attempted to use surfactants with gentamicin solution but found reductions in mechanical properties nevertheless due to the presence of water . Pelleted liposomes, obtained through ultra‐centrifugation in conjunction with amphiphilic polymers (containing a hydrophobic and a hydrophilic portion) may overcome this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al attempted to use surfactants with gentamicin solution but found reductions in mechanical properties nevertheless due to the presence of water. 24 Pelleted liposomes, obtained through ultra-centrifugation in conjunction with amphiphilic polymers (containing a hydrophobic and a hydrophilic portion) may overcome this issue. Non-toxic, neutral surfactants, such as Pluronic block copolymers, which improve the miscibility of solutions, may be employed to overcome phase separation of the liposomes in methyl methacrylate.…”
Section: Introductionmentioning
confidence: 99%
“…PMMA is widely used clinically, although applications are limited due to the nondegradability and slow release of antibiotic. Optimal loading concentrations for PMMA may be determined through modeling and rational selection, although slow release is still a concern requiring porosity inducing additives to improve elution of certain antibiotics . The duration of antibiotic release observed in vitro from sponges was relatively short compared with duration of up to 36 weeks of release from PMMA .…”
Section: Resultsmentioning
confidence: 99%